The impact of the use of elt games and songs in the development of the language oral proficiency of students in the Intensive Intermediate English I in the Foreign Language Department at Universidad de El Salvador. - Sanabria Mejía, Yuri Lisseth; Granadino Gutiérrez, Edwin Josué; Alvarado Escobar, Hugo Oswaldo; Serrano, Verónica Argelia; Ayala, Edgar Nicolás (San Salvador, El Salvador : Universidad de El Salvador, 2014)
The present qualitative and descriptive research project focused on finding out what the impact of the use of songs and games is in the development of the students` language oral proficiency of the Intensive Intermediate English I course in the Foreign Language Department of the University of El Salvador. The research team planned to carry out this project because they realized that songs and games are used in the English class by most teachers. However, the research team also realized that most teachers only use these types of activities in the classroom as warm up and filler activities, which most of the time do not pursue a specific objective to develop students´ oral ability . Hence, by carrying out this qualitative research project, researchers got to understand what the impact of the use of songs and games is in the development of the students` language oral proficiency taking the before mentioned subject. One issue that researchers found is that teachers and students agree on the fact that the use of songs and games can help in the development of the students` oral language proficiency since according to both parts, teachers and students, these activities bring fun to the class, help students learn new vocabulary, among others, which are key factors to develop the language oral proficiency. So, in order to get to know this situation better, the researchers made use of a checklist and administered some questionnaires to the teachers and students involved in the teaching-learning process of the before mentioned course. At the end, researchers understood this issue better by analyzing the data that led researchers to draw to the conclusion of what the impact of the use of songs and games is in the development of the students` language oral proficiency.
Anexos.
Bibliográfia : hojas 40
Keywords: Tecnología educativa; Comunicación oral; Inglés -- Pronunciación; ELT games and songs